University proceedings. Volga region. Social sciences - A.D. Gulyakov; A.Yu. Salomatin (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The problem of creating a federal state on the basis of the Russian Empire, abolished in the spring of 1917, continues to excite more and more researchers with its dramatic nature. The implementation of the transformation, despite the ethnic plu-ralism of Russian civilization, managed to consolidate the new society despite the real dan-ger of national separatism. The article analyzes the difficulties of federalization on the southern borders of the Eurasian power, where in Transcaucasia, the North Caucasus, the Don and Kuban, various models of incorporation of territories into the USSR were used. Materials and methods. The fate of the southern territories during the years of their sovieti-zation, the Civil War and its end is analyzed on the basis of extensive scientific literature. Comparative-historical and comparative-geopolitical methods are used to reveal the topic. Results. It is noted that historically, Transcaucasia and the North Caucasus were the object of expansionist aspirations on the part of the Ottoman Empire and Iran, and at the end of the First World War – Germany and England, which made the restoration of Russian state-hood a particularly difficult task. At the same time, in terms of communication proximity, these territories were more accessible than Siberia and the Far East, although this same ac-cessibility contributed to the success of the anti-Bolshevik forces. The liberation of Trans-caucasia from bourgeois nationalist governments during April 1920-March 1921 was com-pleted by the creation in March 1922 of the Federal Union of Socialist Republics of Transcaucasia, which was the most optimal way to combat manifestations of localism and territorial disputes. The final sovietization of the North Caucasus, Kuban and Don took place in a shorter period of time. By the spring of 1920, the White Guards of A. I. Denikin, the main anti-Bolshevik force, were finished. Taking into account the more complex ethnic composition than in Transcaucasia, the new government began organizing national auton-omies and territorial regions in 1920–1922. Conclusions. The federalization of the southern territories of post-autocratic Russia in 1922–1923 took place according to the same dual scheme used in the western, eastern and southeastern regions – the creation of union repub-lics in the strategic border area and the inclusion of internal autonomies in the RSFSR. On-ly such an approach, with the leading role of the Bolshevik Party, could prevent the danger-ous confederalization of the organized union state and the integration of numerous ethnic groups that were at different stages of social development.